Interventions of Stigma and Discrimination Towards HIV/AIDS Patients: An Integrative Literature Review - Wiwin Martiningsih; Josephine Lorica (Humanistic Network for Science and Technology (HNST), 2018)
HIV / AIDS is a chronic disease that has gained stigma and discrimination. Various attempts had been made by the government to reduce this stigma and discrimination. This paper identified the critical components of interventions with the aim to decrease stigma and discrimination of PLWHA. This integrative literature review was conducted in the databases PubMed and Cumulative Index of Nursing and Allied Health Literature (CINAHL), from January 1, 2007, to December 31, 2017. Finally, 6 studies were found in CINAHL and 2 studies from PubMed. Results revealed that the most interventions were creating a program with a specific designation that aimed to change behavior. Interventions were developed base on diffusion and innovation theory, social cognitive theory, socioeconomic and community theory. Sample articles provided information the positive results, such as 1) decreasing of stigma toward PLWHA from community member, community leader, health worker, community to the family with PLWHA, also from family to PLWHA, 2) improving PLWHA self-esteem, 3) decreasing uncertainty about HIV treatment among PLWHA, 4) increasing institutional support in the hospital, and 5) increasing of HIV knowledge. For further needed programs involving multiple levels of respondents/participants (PLWHA, community, government, organization, health worker, social worker) in one moment and implemented at least 1 year, by combining behavior change techniques through education, social marketing, and community/group organizational development. Keywords: Interventions of stigma, Discrimination, HIV/AIDS